Adoption of open innovation: Evidence from SMEs in the Ghanaian Hospitality Industry - Hongyun, Tian; Kankam, William Adomako; Appiah-Twum, Florence; Akolgo, Isaac Gumah; Iqbal, Shuja; Spio-Kwofie, Adelaide (International Journal of Scientific Research and Management (IJSRM), 2019)
The objective of the study was to analyze the determinants of open innovation adoption among the Ghanaian hospitality SMEs. A cross‐sectional survey using a 5‐point Likert scale questionnaire was used to randomly collect data from 530 managers within the hospitality industry in Ghana. Using SmartPLS software 3.2.8 to analyze primary data, the results show that all six determining factors have a significant impact on open innovation adoption in the hospitality industry. Specifically, competition, human skills, managerial style and IT infrastructure have a positive and significant relationship with open innovation adoption. However, cost and cultural factors had a negative but significant influence on open innovation adoption. The study also provides managers with practical ways of adopting open innovation in the Ghanaian hospitality industry.